(untitled) - Zarrella, Dan (Hoboken, New Jersey, 2013)
Scientific marketing research delivers proven marketing tactics and tips The Science of Marketing applies a scientific approach to the way businesses and brands approach marketing. It uses a combination of marketing, statistical, and psychological research to explain why and, more importantly, how, companies should adapt marketing strategies such as blogging, social media, email marketing, and webinars to achieve maximium results
Keywords: Internet marketing,Tiếp thị internet; Social aspects,Khía cạnh xã hội